Storage linking techniques for the automatic management of dynamically variable arrays - Alarilla, Luis Manuel (1974)
The arrangement of numbers and/or symbols into arrays provides a natural and convenient way of representing data for algorithmic processes to be performed by a computer. This comes about from the ability to reference array elements by specifying the array name together with a set of subscripts. Thus general purpose computers from the earliest models to the present have had array handling capabilities. These capabilities have grown from the ability to work with a one dimensional array or a vector of equal length elements in the early computers to a machine which allows the most general arrays. The changes in array handling capabilities are tied to the changes in the way the memory resource of the computer is organized. This study seeks to determine if the benefits of dynamically variable arrays can be obtained using other schemes at lower cost. Hopefully this paper would provide some help in the search for an organization of general purpose computer systems memory resource which would conveniently accommodate contemporary data representation.